Raymundo Colares and the cinema: from gibis to super-8 films (Palíndromo, 2023)
The disarticulation of visual structures is one of the main issues that Raymundo Colares develops in his poetic journey. This article seeks to answer the close relationship his works evoke with the idea of image movement sensation, a fundamental principle of cinema. For this, it analyzes the series of works that the artist calls Gibi and relates them to the technique of cinematographic montage. In a second moment, the text reflects on the three films that Colares made, seeking to demonstrate how these works are part of his research into visual disarticulation and can also see as a form of painting in motion.
Keywords: Raymundo Colares; artist films; gibi; super-8